2021
DOI: 10.54037/wjps.2021.91201
|View full text |Cite
|
Sign up to set email alerts
|

Sideeffects of Covid-19 vaccines amongpopulation of Karachi-A survey based study

Abstract: In management of Covid-19 many vaccines had developed to date and still 105 vaccines are in clinical trials. According to statistics and research, 6.54 billion doses of covid-19 vaccines have been given to people worldwide till October 2021. After the approval of vaccines by the government of Pakistan, a hyped has been created by citizens of Pakistan about side effects of vaccines. So, we have performed a survey to evaluate the side effects of covid-19 vaccines in population of Karachi this survey is performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a result, when compared to other available vaccinations, the inactivated Sino-pharm and Sinoavac vaccine in the current study reveals a considerably higher safety profile. However, these comparisons should be made with caution because some studies have a small sample size [21], while others have reported some serious adverse effects [22,23]. The majority of vaccines have a few adverse effects, which are frequently The latest survey mentioned that all of the immunization-related adverse effects mentioned were minimal and were handled with paracetamol tablets, which wore off after 1-2 days.…”
Section: Fig 1 Distribution Of Post-vaccination Acute Side Effectsmentioning
confidence: 99%
“…As a result, when compared to other available vaccinations, the inactivated Sino-pharm and Sinoavac vaccine in the current study reveals a considerably higher safety profile. However, these comparisons should be made with caution because some studies have a small sample size [21], while others have reported some serious adverse effects [22,23]. The majority of vaccines have a few adverse effects, which are frequently The latest survey mentioned that all of the immunization-related adverse effects mentioned were minimal and were handled with paracetamol tablets, which wore off after 1-2 days.…”
Section: Fig 1 Distribution Of Post-vaccination Acute Side Effectsmentioning
confidence: 99%